THE USE OF THE COOPERATIVE INTEGRATED READING AND COMPOSITION MODEL ON THE ABILITY OF ECONOMICS STUDENTS - Masni, Harbeng (LLDIKTI Wilayah 1 Sumatera Utara, 2024)
The purpose of the study was to describe the question of how the application of the cooperative integrated reading and composition model affects the writing of economics students. The approach method that will be used in this study is a quantitative approach. The results of this study indicate that the learning model for learning essay writing skills is better than the results of learning to write essays using conventional learning models. Based on the hypothesis testing, it was concluded that the use of the model affects the results of learning to write essays for economics students.